2006
DOI: 10.1007/s10549-006-9277-x
|View full text |Cite
|
Sign up to set email alerts
|

NSAID use and survival after breast cancer diagnosis in post-menopausal women

Abstract: Many epidemiologic studies, although not all, have shown an inverse relation between non-steroidal anti-inflammatory drug (NSAID) use and risk of incident breast cancer, but the possible influence of NSAID use on breast cancer survival has not been evaluated. We examined the association between self-reported NSAID use and survival after invasive breast cancer diagnosis among 591 postmenopausal women in a prospective study. Cox proportional hazards regression was used to estimate the hazard ratios (HRs) and 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 26 publications
(38 reference statements)
2
91
2
Order By: Relevance
“…They found a reduced risk of recurrence for current regular (Ն 3 days per week) use of ibuprofen (RR ϭ 0.56; 95% CI, 0.32 to 0.98) but not aspirin (RR ϭ 1.09; 95% CI, 0.74 to 1.61); short follow-up (5 years) may have precluded detecting an association. Blair et al 34 reported a borderline reduced risk of breast cancer death (RR ϭ 0.64; 95% CI, 0.39 to 1.05) for any use of NSAIDs after diagnosis among 591 postmenopausal women with breast cancer in the Iowa Women's Health Study. In that study, aspirin and nonaspirin NSAID use was combined, but use of aspirin only (43%) was considerably more common than use of nonaspirin NSAIDs only (10%) or use of both (27%).…”
Section: Discussionmentioning
confidence: 99%
“…They found a reduced risk of recurrence for current regular (Ն 3 days per week) use of ibuprofen (RR ϭ 0.56; 95% CI, 0.32 to 0.98) but not aspirin (RR ϭ 1.09; 95% CI, 0.74 to 1.61); short follow-up (5 years) may have precluded detecting an association. Blair et al 34 reported a borderline reduced risk of breast cancer death (RR ϭ 0.64; 95% CI, 0.39 to 1.05) for any use of NSAIDs after diagnosis among 591 postmenopausal women with breast cancer in the Iowa Women's Health Study. In that study, aspirin and nonaspirin NSAID use was combined, but use of aspirin only (43%) was considerably more common than use of nonaspirin NSAIDs only (10%) or use of both (27%).…”
Section: Discussionmentioning
confidence: 99%
“…Blair et al [103] examined effects of NSAID intake on survival after invasive breast cancer diagnosis among 591 postmenopausal women ascertained through the Iowa Women's Health Study. Compared to nonusers, women who regularly took an NSAID experienced a 36% reduction in breast cancer mortality and a 43% reduction in allcause mortality after approximately 10 years of followup.…”
Section: Therapeutic Studies Of Nsaids In Human Breast Cancermentioning
confidence: 99%
“…In breast cancer, a number of observational studies have examined associations between aspirin use and disease recurrence or death (4)(5)(6)(7)(8)(9)(10)(11)(12), with three reporting statistically significant reductions in breast cancer-related mortality (5)(6)(7). Most of these studies included women taking aspirin before their breast cancer diagnosis and did not distinguish between pre-and post-diagnostic initiation of exposure in their analyses (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies included women taking aspirin before their breast cancer diagnosis and did not distinguish between pre-and post-diagnostic initiation of exposure in their analyses (5)(6)(7)(8)(9). Only two previous studies have examined associations between de novo post-diagnostic aspirin use and breast cancer outcomes (11,12).…”
Section: Introductionmentioning
confidence: 99%